Is parental mediation negatively associated with problematic media use among children and adolescents? A systematic review and meta-analysis - Fam, Jia Yuin; Männikkö, Niko; Juhari, Rumaya; Kääriäinen, Maria (Canadian Psychological Association, 2022)
Parents in contemporary society face the challenge of establishing guidelines for how to manage their children’s and adolescent’s media use. Parental mediation, or the parenting strategies for regulating children’s media use, is frequently mentioned in discussions of problematic media use. However, previous research has provided inconsistent findings on the relationship between parental mediation and problematic media use. This systematic review and meta-analysis aimed to investigate the correlation between parental mediation (restrictive-, active-, and co-using mediation) and problematic media use (internet gaming disorder, social media disorder, and general problematic media use) among children and adolescents. Systematic literature searches were conducted in three online databases: Web of Science; Scopus; and EBSCO (CINAHL). PRISMA guidelines on eligibility criteria were observed. This review included a total of 41 studies which involved 47,264 children/adolescents (between 5 and 22 years of age) and 77,494 parents/carers. The initial results revealed that active mediation and co-using mediation are significantly correlated with problematic media use, while a nonsignificant relationship was found between restrictive mediation and problematic media use. Additional subgroup analyses revealed more complex relationships between parental mediation and problematic media use. This study highlighted certain methodological considerations that should be included in future studies to provide reliable evidence for the link between parental mediation and problematic media use.